Lietuvos valdovų insignijos XIII amžiaus pabaigos-XV amžiaus vidurio majestotiniuose antspauduose: ikonografiniai politinės programos ypatumai - Skurvydaitė, Loreta (Lietuvos istorijos studijos, 2004)
Development of the Lithuanian ruler’s status and political context has a direct influence on the formation of seals’ portrayal as well as on the seal, as insignia itself. Royal insignia expressed the ideology and symbolism of the ruler’s power. They played a significant symbolic and sacral role during the coronation ceremony. The oldest royal insignia are the crown, sword, and lance, while the latter lost its significance. Because of the lack of written sources on the coronation and enthronization of Lithuanian kings and grand dukes, seals have enormous advantages over other historical witnesses. The portrayal of figures enriched by additional symbolism gives us a clear impression of what insignia were used. The majesty seals of Mindaugas, Gediminas, Vytautas, Švitrigaila, and Žygimantas Kęstutaitis not only depicted the rulers’ insignia but also help us to reconstruct the political conception of these rulers. Different insignia were attributed to different ranks of rulers. According to the sphragistics materials, Mindaugas, being a king, used insignia of royal rank (an orb surmounted by a cross and a flowered sceptre). Gediminas, being a grand duke, also used insignia of royal rank (an orb and a crown) but with a slight difference: the crown is in his hand but not on his head. The sword, together with the mitra (dukes’ cap), is a very important insignia of grand dukes. The portrayal figures of Vytautas, Švitrigaila, and Žygimantas Kęstutaitis seals have these insignia. The sword, being one of the oldest insignia, was already depicted on the Lithuanian rulers’ seals with mounted and unmounted warriors. The sphragistic data also shows that the sword was a prerogative of rulers and was not used by those who only belonged to the ruling dynasty. Examining the Lithuanian seals’ data, one could prove that the iconographical programme was influenced not only by the medieval sphragistic tradition but also by political aspirations. The seals were not only a sign of authority but also expressed the status of the Lithuanian ruler and political realities during the 13th and 15th centuries. The portrayal figure of the seal conveys, even if sometimes only symbolically, the ideal of the sovereignty of the person using it.